If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 3(9) + -26 Multiply 3 * 9 y = 27 + -26 Combine like terms: 27 + -26 = 1 y = 1 Solving y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 1
| 15+5n=40 | | 2h+9=63 | | 7k^2+37k+7k^2=0 | | 4x-6(-2x-5)=126 | | T/7+4=6 | | 71-x=14-6x | | -4x+6=-74+6x | | -4(w-2)=0-2+2w | | M/4-3=5 | | 20m+1m=3 | | 8x-14=8x+14 | | b^2+6b-55=0 | | 6x-7y=1/2 | | a-8=12+a | | 3(x-3)/2=6 | | (3^1/2+4)/(6^1/2+2) | | 5-0.015x=0.035x | | 35.60/8 | | -11=z-3 | | 15x-15/7*5x-5/42=18 | | 6x^2=40 | | 28/8 | | -6x+4=6x-116 | | 3x-8x=65 | | 9+4(2p-1)=4 | | -2x+(2x+28)=19 | | 5x-9+3=7x-11 | | -14=6+4x | | 2x+2x-5=7 | | 30=4x+2 | | 11x-49=-2 | | u=6-5/4u |